Environmental education from university communal work: the experience of the Alberto Manuel Brenes Biological Reserve, San Ramón, Costa Rica (Biocenosis, 2021)
Abstract: Social action is an essential cornerstone in the work of the University of Costa Rica. The student community service is comprised within the university extension programs, and it is characterized by encouraging communities to become autonomous in the search of solutions to their everyday problems. The Environmental Education Project of the Alberto Manuel Brenes Biological Reserve aims at making the protected area and its natural resources known to people so as to promote its conservation. The project started in 2010 and since then more than 200 students have enrolled in it. This means that at least 64,000 hours of student community service have been carried out in more than 50 educational centers and a similar number of communities. Thanks to this project, the number of people who are now familiar with the biological reserve is undoubtedly higher than before its start.